Ultrastructural and Functional Analysis of a Novel Extra-Axonemal Structure in Parasitic Trichomonads - Coceres, Veronica M.; Iriarte, Lucrecia S.; Miranda-Magalhães, Abigail; Santos de Andrade, Thiago André; de Miguel, Natalia; Pereira-Neves, Antonio (Frontiers in Cellular and Infection Microbiology, 2021)
Trichomonas vaginalis and Tritrichomonas foetus are extracellular flagellated parasites that inhabit humans and other mammals, respectively. In addition to motility, flagella act in a variety of biological processes in different cell types, and extra-axonemal structures (EASs) have been described as fibrillar structures that provide mechanical support and act as metabolic, homeostatic, and sensory platforms in many organisms. It has been assumed that T. vaginalis and T. foetus do not have EASs. However, here, we used complementary electron microscopy techniques to reveal the ultrastructure of EASs in both parasites. Such EASs are thin filaments (3–5 nm diameter) running longitudinally along the axonemes and surrounded by the flagellar membrane, forming prominent flagellar swellings. We observed that the formation of EAS increases after parasite adhesion on the host cells, fibronectin, and precationized surfaces. A high number of rosettes, clusters of intramembrane particles that have been proposed as sensorial structures, and microvesicles protruding from the membrane were observed in the EASs. Our observations demonstrate that T. vaginalis and T. foetus can connect to themselves by EASs present in flagella. The protein VPS32, a member of the ESCRT-III complex crucial for diverse membrane remodeling events, the pinching off and release of microvesicles, was found in the surface as well as in microvesicles protruding from EASs. Moreover, we demonstrated that the formation of EAS also increases in parasites overexpressing VPS32 and that T. vaginalis-VPS32 parasites showed greater motility in semisolid agar. These results provide valuable data about the role of the flagellar EASs in the cell-to-cell communication and pathogenesis of these extracellular parasites.